Students' Ability in Speaking on YouTube Video Project - I Gusti Agung Vony Purnama (Fakultas Bahasa Asing (FBA) Universitas Mahasaraswati Denpasar, 2025)
English speaking is an essential skill that must be learned by higher education students, in this case is the EFL students. Speaking skill is very useful and needed for their future to increase their chance in getting the future job worldwide. English is the core subject in higher education; therefore, the students must enrol to complete their studies. However, this skill is difficult to master since they do not speak English in their everyday life. This present study aims to determine the students' ability to speak on their YouTube video project. There were four components of speaking used in this study. They were Pronunciation, Fluency, Grammar, and Vocabulary. The students’ YouTube video projects were used as the data to see their ability in speaking. It was found that the highest average score is on the component of Grammar among the four components of speaking. Then, it is followed by Vocabulary, Pronunciation, and the lowest is on the Fluency component. The average score of their speaking is 72.7, hence, it can be concluded that the students’ speaking ability on their YouTube video project is in a good category. The use of YouTube in speaking is effective to improve the students’ speaking ability. Overall, this study contributes on the research of the same field on the English language teaching for EFL students in exploring the effectiveness of the technological enhancement to help the students improving their speaking skills.